The Management Standards Indicator Tool and the estimation of risk - Bevan, Adrian; Houdmont, Jonathan; Menear, Nicholas (Oxford Journals, 2010)
Background: The Health & Safety Executive’s (HSE) Indicator Tool offers a measure of exposure to psychosocial work conditions that may be linked to stress-related outcomes. The HSE recommends that Indicator Tool data should be used as a basis for discussions concerned with the identification of psychosocial work conditions that might warrant prioritisation for intervention. However, operational constraints may render discussions difficult to convene and, when they do take place, the absence of information on harms associated with exposures can make it difficult to identify intervention priorities. Aims: To examine (1) the utility of the Indicator Tool for the identification of a manageable number of psychosocial work conditions as intervention candidates and (2) whether administration of a measure of stress-related outcomes alongside the Indictor Tool can facilitate the identification of intervention priorities. Methods: 1,038 employees in the London region of the Her Majesty’s Prison Service completed the Indicator Tool and a measure of psychological well-being. Odds ratios were calculated to estimate the risk of impairment to well-being associated with exposure to psychosocial work conditions. Results: The Indicator Tool identified 34 psychosocial work conditions as warranting improvement. Intervention priority was given to those working conditions that were both reported to be poor by ≥ 50% of respondents and associated with risk of impairment to well-being. This method allowed for the identification of four areas. Conclusions: Augmentation of the Indicator Tool with a measure of stress-related outcomes, and the calculation of simple risk estimation statistics, can assist the prioritisation of intervention candidates.